Factors Influencing Parents' Preferences and Parents' Perceptions of Child Preferences of Picturebooks - Wagner, Laura (Frontiers in Psychology, 2017)
This study examined factors influencing parents’ preferences and their perceptions of their children’s preferences for picturebooks. First, a content analysis was conducted on a set of picturebooks (N = 87) drawn from the sample described in Wagner (2013); Then, parents (N = 149) rated the books and several content properties were examined for their ability to predict parents’ preferences and their perception of their children’s preferences. The initial content analysis found correlated clusters of disparate measures of complexity (linguistic, cognitive, narrative) and identified a distinctive sub-genre of modern books featuring female protagonists. The later preference analysis found strong influences of gender, with parents perceiving their sons’ (but not daughters’) preferences as gender-stereotyped; in addition, influences of the child’s reading ability and the linguistic complexity of the book on preferences suggested a sensitivity to the cultural practice of joint book-reading.